Software In the Loop Simulation for Robot Manipulators - Ben Ayed, M.; Zouari, L.; Abid, M. (Engineering, Technology & Applied Science Research, 2017)
In the last decades, the classical verification of robotic software component is postponed until the code is developed enough to function in real hardware. For this reason, the verification of code at early stages is essential to reduce development costs and necessary time for embedded systems such as robot manipulator. Therefore, Software In the Loop (SIL) simulation may be realized in the early stages of software development. It offers the possibility to execute tests before the hardware is available and thus detect errors. In this paper, we propose a Software In the Loop (SIL) test for robot manipulator driven by a Brushless DC Motor without a target system hardware. Simulation results prove the rapidity and the good performance of the developed code for the controller’s part by the validation of the behavior of robot manipulator software.